2005
DOI: 10.1111/j.1600-0609.2005.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of cardiac dysfunction in thalassemic patients by radionuclide angiography and heart rate variability analysis

Abstract: Right ventricular dysfunction and abnormal HRV may represent the early features of cardiac disease in thalassemic patients with no evidence of ventricular dysfunction at routine evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 24 publications
0
30
0
1
Order By: Relevance
“…In the early stage, patients are usually asymptomatic. Restrictive cardiomyopathy usually occurs before dilated cardiomyopathy (7), in accordance with diastolic dysfunction, which normally happens before systolic dysfunction and overt heart failure (8)(9)(10)(11)(12).…”
Section: Clinical Insightmentioning
confidence: 99%
See 4 more Smart Citations
“…In the early stage, patients are usually asymptomatic. Restrictive cardiomyopathy usually occurs before dilated cardiomyopathy (7), in accordance with diastolic dysfunction, which normally happens before systolic dysfunction and overt heart failure (8)(9)(10)(11)(12).…”
Section: Clinical Insightmentioning
confidence: 99%
“…Left-sided heart failure is clinically more common than right-sided heart failure (12). However, it has been shown that right ventricular dysfunction develops earlier in asymptomatic TM patients (9,17).…”
Section: Clinical Insightmentioning
confidence: 99%
See 3 more Smart Citations